2010
DOI: 10.1177/1753465809358249
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with chronic cough

Abstract: Chronic cough is a relatively common symptom for which effective, acceptable treatments are lacking. Many patients suffer frequent coughing over several years without resolution and this has significant physical, social and psychological consequences. The recent development of cough-specific quality-of-life tools now allows quantification of the burden of coughing both in patients specifically presenting with chronic cough and also in common respiratory conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 40 publications
0
60
0
1
Order By: Relevance
“…While there is no research focusing exclusively on the experience of cough in patients with lung cancer, studies conducted with chronic cough patients or those with other respiratory diseases such as asthma and chronic obstructive pulmonary disease suggest that cough is a distressing symptom with a significant impact on daily life [1,2]. Kelsall et al [3] recently found that chronic cough patients coughed an average 13.9 times/hour, with many coughing hundreds of times each day.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…While there is no research focusing exclusively on the experience of cough in patients with lung cancer, studies conducted with chronic cough patients or those with other respiratory diseases such as asthma and chronic obstructive pulmonary disease suggest that cough is a distressing symptom with a significant impact on daily life [1,2]. Kelsall et al [3] recently found that chronic cough patients coughed an average 13.9 times/hour, with many coughing hundreds of times each day.…”
Section: Introductionmentioning
confidence: 98%
“…Numerous other effects of coughing, e.g. chest pains, rib fractures, hernia, stress incontinence, headaches and physical exhaustion, have been reported [2].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic or dry cough is not a life-threatening disease in most of the cases but it affects seriously the healthcare budget and the quality of life [14][15][16]. This is a topical and multi-factorial pathology, requiring a pluri-targeted treatment approach [17].…”
Section: Discussionmentioning
confidence: 99%
“…It is an essential protective and defensive action that secures the removal of mucus, noxious substances, and infections from the larynx, trachea, and larger bronchi (Chung, 2003). On the other hand, a number of patients have a non-productive cough, which is not associated with mucus clearance and may be the first overt sign of disease of the airways or lungs, may significantly contribute to the spread of airborne infections, and in some instances may result in severe functional and structural damage to the organism (for review, see Irwin et al, 2006;Brignall et al, 2008;Young & Smith, 2010).…”
Section: Introductionmentioning
confidence: 99%